Integration of regional innovation platforms through inter-level networking - O. V. Potasheva; M. V. Kuzmenko; M. I. Plutova (Открытое образование (Москва))
Purpose of the study. Innovative platforms as an institute for the development of innovative activities in the education system are the technological basis for the formation of a regional innovation and educational network. The development and use of models of network interaction between educational organizations is an effective tool. The purpose is to describe the development of a regional model of inter-level network interaction of educational organizations and the results of its testing to disseminate the experience of creating innovative educational resources and the development of digital educational professional communities. The article discusses the main problems of development and improving the quality of education of all types and levels using digital technologies in Russian system of education.Materials and methods. The methods of analysis and comparison of domestic and foreign theory of the development of the educational system are used. The study of the model of innovative pedagogy as means of adapting the education system to the new challenges of the 21st century helps to identify effective methods of improving in the implementation of innovative projects and programmes, using information and communication technologies in the modern system of regional education through inter-level integration. To study the effectiveness of the implementation of the network interaction model, we used the results of a survey of participants in the network professional community of regional innovative educational platforms.Study results. The study showed that the use of digital technologies, in particular, when creating new network resources for the interaction of regional innovation platforms, has a positive impact on the level and quality of implementation of innovative projects and programs. A model of the organization of network interaction of regional innovative educational platforms is presented, which shows that to a greater extent it helps to unleash the creative potential of teams of educational organizations located in rural areas. The level of involvement and motivation of all members of the community to set and achieve a goal, search for a collective solution and develop recommendations for improving the educational process in the online communication mode is increasing. The positive emotional influence of network interaction on productivity and quality of work, the mood of teachers is noted. A number of problem areas were identified in the process of creating innovative platforms, the elimination of which will contribute to increasing the efficiency of the digitalization process in education.Conclusion. A significant contribution to the development of the regional education system is made by the activity of innovative platforms created with the aim of testing and further disseminating successful advanced pedagogical experience in the region. The proposed model of network interaction of regional innovation platforms shows the possibility of overcoming differences in the conditions of subjects of education to be combined in digital professional communities and contributes to the implementation of successful innovative teaching practices. The results of the study can be useful for institutions of educational development at the regional level of management and development of interconnection of participants in the educational process.